Effects of training and anthropometric factors on marathon and 100 km ultramarathon race performance - Tanda G; Knechtle B (Dove Medical Press, 2015)
Giovanni Tanda,1 Beat Knechtle2,3 1Polytechnic School, University of Genoa, Genoa, Italy; 2Gesundheitszentrum St Gallen, St Gallen, 3Institute of Primary Care, University of Zurich, Zurich, Switzerland Background: Marathon (42 km) and 100 km ultramarathon races are increasing in popularity. The aim of the present study was to investigate the potential associations of anthropometric and training variables with performance in these long-distance running competitions. Methods: Training and anthropometric data from a large cohort of marathoners and 100 km ultramarathoners provided the basis of this work. Correlations between training and anthropometric indices of subjects and race performance were assessed using bivariate and multiple regression analyses. Results: A combination of volume and intensity in training was found to be suitable for prediction of marathon and 100 km ultramarathon race pace. The relative role played by these two variables was different, in that training volume was more important than training pace for the prediction of 100 km ultramarathon performance, while the opposite was found for marathon performance. Anthropometric characteristics in terms of body fat percentage negatively affected 42 km and 100 km race performance. However, when this factor was relatively low (ie, less than 15% body fat), the performance of 42 km and 100 km races could be predicted solely on the basis of training indices. Conclusion: Mean weekly training distance run and mean training pace were key predictor variables for both marathon and 100 km ultramarathon race performance. Predictive correlations for race performance are provided for runners with a relatively low body fat percentage. Keywords: running, performance, training indices, body fat, sports training